Recent Advances in Lead-Free All-Inorganic Perovskite CsCdCl3 Crystals for Anti-Counterfeiting Applications - Nankai Wang; Zhaojie Zhu; Jianfu Li; Chaoyang Tu; Weidong Chen; Yan Wang (Crystals)
This study reviews the advanced anti-counterfeiting applications of CsCdCl3, a lead-free all-inorganic perovskite crystal exhibiting dynamic luminescent properties responsive to temperature and UV light. Using synthesis methods such as Bridgman and hydrothermal techniques and incorporating dopants like bromine and tellurium, this research achieves improved luminescent stability, spectral diversity, and afterglow characteristics in CsCdCl3. The crystal demonstrates extended afterglow, photochromic shifts, and temperature-sensitive luminescence, enabling applications in 4D encoding for secure data encryption and in cold-chain temperature monitoring for pharmaceuticals. Despite these promising attributes, the challenges related to photostability, batch consistency, and environmental resilience persist, necessitating further exploration into the optimized synthesis and doping strategies to enhance material stability. These findings underscore the potential of CsCdCl3 for high-security information storage, pharmaceutical anti-counterfeiting, and real-time environmental sensing, positioning it as a valuable material for the next generation of secure, intelligent packaging solutions.